2021
DOI: 10.1007/s00044-021-02754-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and anticancer evaluation of nitrogen-substituted 1-(3-aminoprop-1-ynyl)-4-hydroxyanthraquinone derivatives

Abstract: Anthraquinones are of signi cant interest due to their biological activity, coloring properties and synthetic applications. Here, we describe a mild and convenient method for modi cation of 1-ethynyl-4hydroxyanthraquinone that was obtained from the Sonogashira reaction of 1-hydroxy-4iodoanthraquinone with alkynes. The copper(I) catalyzed one-pot three component reaction (A 3 -coupling) of the new 1-ethynyl-4-hydroxyanthraquinone with secondary amines and formaldehyde was the main approach for the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Further, the molecular binding studies of the synthesized compounds towards DNA G-quadruplex revealed that almost all the derivatives showed good binding affinities towards DNA motifs. 126 In yet another research study, 2,6-disubstituted amido anthracene-9,10-dione dimeric distamycin derivatives were designed and synthesized. Among all the synthesized derivatives, the disubstituted anthraquinone with tri- N -methylpyrrole side chain (ANTP) was found to be more promising and exhibited good activity towards c-Myc G-quadruplex DNA with a binding affinity of 3.8 ± 0.01 × 10 6 M −1 .…”
Section: Development Of Target-specific Cytotoxic Anthraquinone Deriv...mentioning
confidence: 99%
“…Further, the molecular binding studies of the synthesized compounds towards DNA G-quadruplex revealed that almost all the derivatives showed good binding affinities towards DNA motifs. 126 In yet another research study, 2,6-disubstituted amido anthracene-9,10-dione dimeric distamycin derivatives were designed and synthesized. Among all the synthesized derivatives, the disubstituted anthraquinone with tri- N -methylpyrrole side chain (ANTP) was found to be more promising and exhibited good activity towards c-Myc G-quadruplex DNA with a binding affinity of 3.8 ± 0.01 × 10 6 M −1 .…”
Section: Development Of Target-specific Cytotoxic Anthraquinone Deriv...mentioning
confidence: 99%